(+)-Neocadambine A and (-)-nauclederine isolated from the bark of Neolamarckia cadamba (Rubiaceae) as natural advanced glycation end products (AGEs) inhibitors - Noor Aimi Othman; Liew, Sook Yee; Blanchard, Patricia; Derbré, Séverine; Chong, Soon-Lim; Abdul Manaf Ali; Khalijah Awang (Penerbit Universiti Kebangsaan Malaysia, 2022)
The phytochemical study on the dichloromethane extract of Neolamarckia cadamba (Roxb.) Bosser has afforded two indole alkaloids, (+)-neocadambine A (1) and (-)-nauclederine (2). Their structures were confirmed by extensive spectroscopic analysis and by comparing with the reported data. (+)-Neocadambine A (1) and (-)-nauclederine (2) exhibited potent inhibition activity of advanced glycation end products (AGEs) with IC50 values of 1.2 and 0.95 mM, respectively, while the latter was almost two times more potent than the standard, aminoguanidine (1.8 mM). This is the first report on the compounds isolated from this plant with AGEs inhibition activity. In addition, (-)-nauclederine (2) was isolated for the first time in the genus of Neolamarckia. Complete 1H-NMR and 13C-NMR of compound 2 were also reported.